2013
DOI: 10.1302/0301-620x.95b5.31047
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement for patients with active tuberculosis of the hip

Abstract: The timing of total hip replacement (THR) in patients with active tuberculosis (TB) of the hip is controversial, because of the potential risk of reactivation of infection. There is little information about the outcome of THR in these patients. We conducted a systematic review of published studies that evaluated the outcome of THR in patients with active TB of the hip. A review of multiple databases referenced articles published between 1950 and 2012. A total of six articles were identified, comprising 65 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…Although one-stage THA is considered as a safe procedure for most patients with advanced active TB of the hip by some authors [ 24 ], our practical experience shows that two-stage THA is an alternative option to treat this challenging disease under some difficult conditions. The hip with sinus tracts or destroyed extensively with difficulties of thorough debridement at one operation may be indications of two-stage THA.…”
Section: Resultsmentioning
confidence: 99%
“…Although one-stage THA is considered as a safe procedure for most patients with advanced active TB of the hip by some authors [ 24 ], our practical experience shows that two-stage THA is an alternative option to treat this challenging disease under some difficult conditions. The hip with sinus tracts or destroyed extensively with difficulties of thorough debridement at one operation may be indications of two-stage THA.…”
Section: Resultsmentioning
confidence: 99%
“…Total hip arthroplasty (THA) in the hip with active tuberculous infection is a controversial issue due to the potential risk of reactivation of TB. 26 The acceptability of the THA is gradually increasing globally [Figure 6a and b ] with reports that metal can be safely used in tuberculous lesions. 5 10 THA in a patient with healed TB of the hip is now an accepted procedure 27 28 29 Majority perform it in the stage of the advance arthritis or in sequalae of advance arthritis when the joint is unsalvageable.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“… 27 31 Kim et al . 26 evaluated the outcome of THR in patients with active TB of the hip in referenced articles published between 1950 and 2012. A total of 65 patients of histologically confirmed TB were reviewed with a mean followup was 53.2 months (24-108).…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sidhu AS et al, 27 Yong qing Wang et al 28 , Kim et al 29 in their respective studies also concluded that THR in patients with active TB of the hip is a safe procedure. If undertaken in association with extensive debridement and appropriate anti-TB treatment, it provides symptomatic relief and functional improvement.…”
Section: Observation and Resultsmentioning
confidence: 95%